Lost in translation: Understanding the possession of digital things in the Cloud - Odom, William; Sellen, Abigail; Harper, Richard; Thereska, Eno (Proceedings of CHI 2012, 2012)
People are amassing larger and more diverse collections of digital things. The emergence of Cloud computing has enabled people to move their personal files to online places, and create new digital things through online services. However, little is known about how this shift might shape people’s orientations toward their digital things. To investigate, we conducted in depth interviews with 13 people comparing and contrasting how they think about their possessions, moving from physical ones, to locally kept digital materials, to the online world. Findings are interpreted to detail design and research opportunities in this emerging space.